PENILAIAN GREENSHIP NEW BUILDING VER 1.2 PADA PROYEK ASRAMA AL-HIKAM DEPOK DAN ESTIMASI BIAYA UNTUK MENINGKATKAN KUALIFIKASINYA - Budi, Agung Setia; Arifin, Syamsul; Soetjipto, Jojok W. (Politeknik Negeri Jakarta, 2024)
The Intergovernmental Panel on Climate Change (IPCC), one of the United Nations' bodies tasked with evaluating climate change science, has reported that humans have experienced temperatures 1.2 degrees Celsius higher than usual, and in the past decade, sea levels have risen almost three times. One of the solutions to this issue is to implement environmentally friendly construction. Asrama Al-Hikam Depok is one of the ongoing construction projects, and this research will examine whether this project applies environmentally friendly construction in its planning. Therefore, it is necessary to identify green building criteria for this dormitory's construction. The method used to identify green building criteria is the Greenship New Building Ver 1.2 method, and the cost estimate is calculated using the latest AHSP method. The results of the criteria achieved by the Asrama Al-Hikam Depok project received a score of 36 out of 101 points, or 36% of the criteria achieved. There are several criteria that can be recommended to increase the rating, provided that the criteria are applied to the building, and of course, there is an additional cost from the initial building budget. The conclusion of this research is that the Greenship rating achieved at the Asrama Al-Hikam Depok project is a bronze rating and can be raised to a silver rating by applying six criteria: Make a statement for temperature and humidity surveys; have a solid construction waste management SOP; have a liquid construction waste management SOP; add lux sensors to workspaces; install CO2 and exhaust sensors in the multipurpose room; install solar panels. The additional cost that can raise the rating of this building by one level above the achieved rating is Rp. 12,298,330.